Come, I Will Walk With You (LEARNing Landscapes, 2024)
A cancer diagnosis enlivens the question of what it means to live well with the Earth and its multidimensional beings, including the children I teach. A cancer diagnosis provides a necessary push to step out from the confines of a self and toward and into the wild fray of this life. I interpret my lived experiences through the practical philosophy of hermeneutics. Hermeneutics has helped me perform and write my lived experience, which I hope will draw in readers and listeners to a recognition of their inescapable ecological interdependence. Cultivating an ability to listen and interpret the world and the human and more-than-human kinships is important to me. Listening to words that children speak helps me learn to be open to the fullness of life, how life is lived, how life can be remembered and suffered and let go. I am gathering sense of being in the world and of understanding the offering that arrives when I nurture a commitment to care for the Earth.
Keywords: Cancer; Hermeneutics; Education; Stories; Lived Experience